Urinary Mercury concentrations associated chewing gum in students of Faculty of Dentistry (Mustansiria Dental Journal, 2018)
The aim of this study was to measure the urinary mercury concentration instudents after chewing gum for certain period of time. Sixteen students from facultyof dentistry had used chewing gum for five hours a day for seven days. Urine samplecollected 24 h before and after the experimental time. Total mercury in urine (U-Hg)was determined by means of inductively coupled plasma mass spectrometry (ICPMS).t-test was used for the comparison of mercury before and after chewing gum. Anon significant difference was found after chewing than before chewing gum.